1999
DOI: 10.1159/000006979
|View full text |Cite
|
Sign up to set email alerts
|

Role of Coronary Angiography in Myxoma Patients: A 14-Year Experience in One Medical Center

Abstract: Cardiac myxoma is the most common form of primary heart tumor and often treated with surgical resection without a preoperative angiographic examination for fear of potential risk of sudden death. During the last 14 years, 24 of 38 patients with myxoma underwent coronary angiography. Coronary artery disease (CAD) and other abnormalities were found in 5. Our findings indicated that CAD is not uncommon among the myxoma patients, and coronary angiography should be performed preoperatively in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Some previous publications showed a prevalence of coronary artery disease between 0 and 11% in patients with myxoma 2 . However, two recent studies showed values between 20.3 and 36.6%, more compatible with the age range of these patients for whom a higher percentage of risk factors for atherosclerosis such as systemic hypertension and dyslipidemia is observed 1,2 .…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Some previous publications showed a prevalence of coronary artery disease between 0 and 11% in patients with myxoma 2 . However, two recent studies showed values between 20.3 and 36.6%, more compatible with the age range of these patients for whom a higher percentage of risk factors for atherosclerosis such as systemic hypertension and dyslipidemia is observed 1,2 .…”
Section: Discussionsupporting
confidence: 54%
“…Some authors support the idea that all patients should undergo cardiac surgery as soon as the diagnosis is made, without previous angiographic examination, basing this assumption on the risk of sudden death 2,4,5 . Others consider coronary angiography a mandatory test only for patients with anginal symptoms or over forty years of age 1,2,4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dear Sir, I read with interest the recent article on the role of coronary arteriography in myxoma patients by Li et al [1]. Besides detecting and quantifying the severity of coexisting coronary artery disease, selective coronary arteriography is also useful in diagnosing cardiac myxoma per se.…”
mentioning
confidence: 99%